2012
DOI: 10.1111/j.1742-4658.2011.08449.x
|View full text |Cite
|
Sign up to set email alerts
|

How myosin motors power cellular functions – an exciting journey from structure to function

Abstract: Molecular motors such as myosins are allosteric enzymes that power essential motility functions in the cell and structural biology is an important tool to decipher how these motors work. Force is produced by myosins upon the actin-driven conformational changes that control the sequential release of the hydrolysis products of ATP (Pi followed by ADP). These conformational changes are amplified by a “lever arm” that includes the region of the motor known as the converter and the adjacent elongated light chain bi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 61 publications
0
16
0
Order By: Relevance
“…The freeenergy changes are computed separately for the unbound state and the IS and OS bound states. Increasing the Mg 2 + polarizability by 10 %, from 0.08 to 0.09 3 , has a very small effect and reduces DG bind by only …”
Section: Tuning Force-field Parametersmentioning
confidence: 97%
See 1 more Smart Citation
“…The freeenergy changes are computed separately for the unbound state and the IS and OS bound states. Increasing the Mg 2 + polarizability by 10 %, from 0.08 to 0.09 3 , has a very small effect and reduces DG bind by only …”
Section: Tuning Force-field Parametersmentioning
confidence: 97%
“…Many proteins perform energy or information transfer with the help of the nucleotide ligands ATP and ADP, or GTP and GDP. [2,3] Many of these phosphates must interact with magnesium. Mg 2 + has an approximately 50 mm concentration in vivo and has been associated with major physiological processes, including cancer and aging.…”
Section: Introductionmentioning
confidence: 99%
“…Following hydrolysis, it is clear that P i must exit the nucleotide-binding pocket by a path that differs from that of ATP entry, as Mg 2+ ?ADP, switch I and switch II completely cover the P i in both kinesin and myosin. It has been suggested that P i release in myosin occurs through a 'back door' opening at the back of the active site, which is observed in a number of myosin structures (Yount et al, 1995;Sweeney and Houdusse, 2010;Llinas et al, 2012). However, this opening is not observed in the rigor-like myosin structures.…”
Section: Frontmentioning
confidence: 80%
“…Following ATP hydrolysis, switch I undergoes movements that disrupt the P i tube and open the active site, providing a pathway for release of P i (bottom). This pathway differs from the 'back door' opening in the active site that has been proposed to provide an exit route for P i release (Yount et al, 1995;Sweeney and Houdusse, 2010;Llinas et al, 2012), but is now considered unlikely (Lawson et al, 2004;Kaliman et al, 2009). Formation of a P i tube by switch I appears to facilitate ATP hydrolysis and also helps explain the essential role of switch I in the catalytic cycle.…”
Section: Frontmentioning
confidence: 99%
“…5C). This myosin also did not perform in the TIRF assay, either because the concentration needed to dimerize the myosin VI using cargo was prohibitively high for detection using TIRF or because of the well-documented decrease in affinity between myosins and actin in high-salt conditions (45,46).…”
Section: Lovdab Controls Myosin VI Recruitment With High Spatial and mentioning
confidence: 99%